TECHNOLOGY AND LEGAL CHALLENGES OF CONTEMPORARY ARMED CONFLICT - Samakashvili, Ana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to research the relationship between IHL, IHRL and national law norms, and to give recommendations about the prevention of using technologies in contemporary armed conflicts. Research methods: in the article, the research was carried out using the comparative-legal method in order to present the relationship between international and national legal norms. Also, we will use the normative method to emphasize the need of introduction of new norms to regulate the problem. Results: after the World War II, adoption of the new international norms significantly decreased the war statistics, however, in recent years, development of technologies, which was further accelerated by the pandemic, changed the mentioned statistics, to the extent that new technologies are actively used in war. Unfortunately, preventive and/or prohibitive international norms do not exist, therefore, we do not have the practice of regulating them. Paucity of regulative norms and the absence of proper literature in this field underscores the relevance of this topic. The use of new technologies can lead to violations of the principles of international law and human rights, which requires the creation of preventive mechanisms within the framework of international law. Discussion: the relevance of the topic is also determined by the war situation in the world, which reminds us that against the backdrop of challenges in international law, there is a gap in terms of illegal integration of technologies in contemporary armed conflicts, which, as a result, leads to a breach of human rights and violation of the norms of both the Geneva Convention and the European Convention on Human Rights.